Assesment of Serum Magnesium Level in Postmenopausal Women With Osteoporosis - Marjan Mahdavi Roshan; Maryam Khazdooz; Parizad Jaraghijoo; Mehrangiz Ebrahimi Mamaghani (Sālmand, 2010)
Objectives: This study was designed to assess nutritional and biochemical factor of magnesium in postmenopausal osteoporotic women.